(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This research article presents a comprehensive analysis of endoscopic hemostasis methods for bleeding from varicose veins of the esophagus. With an alarming mortality rate due to liver cirrhosis and its complications, addressing bleeding from esophageal varices has become a critical medical challenge. This work focuses on the evaluation of traditional and modern techniques, examining their efficacy and safety, and offers new insights into the implementation of endoscopic sclerotherapy and ligation. The study draws on clinical experiences and statistical analyses to propose improvements in endoscopy techniques, analyze the epidemiology of the condition, and provide a critical evaluation of current treatment methods. The article also highlights clinical recommendations for the integration of new methods into practice and outlines perspectives for further research.